Correlation between age, nationality and results of elite ski racers between 1982 and 2025 - Ivanova, I. G.; Novikova, N. B.; Beleva, A. N.; Kotelevskaya, N. B. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to investigate the relationship between the age and nationality of athletes and their performance at various distances in World Cups, World Championships and Olympic Games between 1982 and 2025 in order to identify current trends in the development of the sport.